Formulasi dan Uji Aktivitas Antioksidan Sediaan Essence Ekstrak Etanol Bunga Telang (Clitoria ternatea L.) dengan Variasi Konsentrasi Butilen Glikol - Freshananda Dzulhija, Aleyda; Aisiyah, Siti; Harjanti, Reslely (Sekolah Tinggi Ilmu Kesehatan Nasional & Pengurus Cabang Ikatan Apoteker Indonesia (IAI) Sukoharjo, 2024)
Telang flowers (Clitoria ternatea L.) contain polyphenolic compounds with the main component, anthocyanins, which have high antioxidant properties. The application of antioxidants as skin protection agents is made in the form of essence preparations. The purpose of this research is to make a preparation of ethanol extract of telang flower with varying concentrations of butylene glycol to obtain a formula with the best physical quality and stability and has antioxidant activity. The ethanol extract of telang flower was obtained from the maceration process using 70% ethanol solvent, then the essence formula was made with variations in the concentration of butylene glycol as a humectant, namely 5%; 7,5%; 10%. Physical quality test of essence preparation includes organoleptical observation, homogeneity, viscosity, pH, and stability test using Freeze-Thaw method. Testing the antioxidant activity of essence preparations using the DPPH method. The data obtained were analyzed using SPSS. The results of the research show that the ethanol extract of telang flower can be made into an essence preparation with good physical quality, where variations in the concentration of butylene glycol affect the viscosity of the preparation, namely the higher the concentration of butylene glycol, the thicker the resulting essence preparation. The formula with a concentration of 5% butylene glycol, has good physical quality, is stable in organoleptic and homogeneity and has antioxidant activity against DPPH (2,2-diphenyl-1-picrylhydrazyl) free radicals.